Melatonin enhanced low-temperature combined with low-light tolerance of pepper (Capsicum annuum L.) seedlings by regulating root growth, antioxidant defense system, and osmotic adjustment - Li, Jing; Xie, Jianming; Yu, Jihua; Lyv, Jian; Zhang, Junfeng; Ding, Dongxia; Li, Nenghui; Zhang, Jing; Bakpa, Emily Patience; Yang, Yan; Niu, Tianhang; Gao, Feng (Frontiers in Plant Science, 2022)
Melatonin (MT) is an important biologically active hormone that plays a vital role in plant growth and development. In particular, it has been investigated for its roles in abiotic stress management. In this study, pepper seedlings were subjected to low-temperature combined with low-light stress (LL) (15/5°C, 100/0 μmol m-2s-1) prior to a foliar spray of 200mM MT for 168h to investigate the protective role of MT in pepper seedlings. Our results demonstrated that LL stress negatively affected root growth, and accelerated the accumulation of reactive oxygen species (ROS), including H2O2 and O2-, changed the osmolytes contents, and antioxidative system. However, these were reversed by exogenous MT application. MT effectively promoted the root growth as indicated by significant increase in root length, surface area, root volume, tips, forks, and crossings. In addition, MT reduced the burst of ROS and MDA contents induced by LL, enhanced the activities of SOD, CAT, POD, APX, DHAR, and MDHAR resulted by upregulated expressions of CaSOD, CaPOD, CaCAT, CaAPX, CaDHAR, and CaMDHAR, and elevated the contents of AsA and GSH, declined DHA and GSSH contents, which prevented membrane lipid peroxidation and protected plants from oxidative damages under LL stress. Furthermore, seedlings treated with MT released high contents of soluble sugar and soluble protein in leave, which might enhance LL tolerance by maintaining substance biosynthesis and maintaining cellular homeostasis resulted by high levels of osmolytes and carbohydrate in the cytosol. Our current findings confirmed the mitigating potential of MT application for LL stress by promoting pepper root growth, improving antioxidative defense system, ascorbate-glutathione cycle, and osmotic adjustment.